Multi-robot control for a static polygon formation using Neighbor-Leader algorithm - Bayadir A. Issa; Abdulmuttalib Turky Rashid (Journal of King Saud University: Computer and Information Sciences)
One of the biggest open challenges to the robotic system is controlling robots formation. Its importance has been noted in a wide variety of applications, from truck platoons to robot-based standalone parcel delivery. In this paper, a new central approach to controlling a polygon-shaped formation called the Neighbor-Leader Algorithm is proposed for a group of neighbor robots randomly distributed in an unknown environment. Firstly, a localization procedure for multi-robots is used to estimate the real-time positions and orientations of a leader robot and its neighbor robots. This information is collected using an equipped RP LIDAR sensor on each robot then the collected information is sent to the leader one. Secondly, neighbor robots are rearranged into a regular distribution by moving them around the leader one in circular paths to produce a new distribution with equal angles between each two neighbor robots. In the last step, the direction of each neighbor robot is changed toward the leader robot. After that, all neighbor robots move towards the leader until they reach a virtual circle that passes through the required polygon vertices. The simulation results illustrate the integrity of this algorithm.